2012
DOI: 10.1590/s0100-204x2012000900024
|View full text |Cite
|
Sign up to set email alerts
|

Modelos de elevação para obtenção de atributos topográficos utilizados em mapeamento digital de solos

Abstract: Resumo -O objetivo deste trabalho foi avaliar modelos digitais de elevação (MDE), obtidos por diferentes fontes de dados, e selecionar um deles para derivar variáveis morfométricas utilizadas em mapeamento digital de solos. O trabalho foi realizado na Bacia Guapi-Macacu, RJ. Os dados primários utilizados nos modelos gerados por interpolação (MDE-carta e MDE-híbrido) foram: curvas de nível, drenagem, pontos cotados e dados de sensor remoto transformados em pontos. Utilizaram-se, na comparação, modelos obtidos p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
1
10
0
7
Order By: Relevance
“…This was observed by Pinheiro et al (2012), who evaluated the quality of the DEM derived from the topographic map, ASTER and SRTM in a qualitative assessment based on the aspects of the surface and a number of spurious depressions, for a DSM in a watershed of 125,078 ha, with relief variation from flat to rugged. These authors observed a better performance of DEM-TM and hybrid DEM (map data + data points extracted from SRTM + points extracted from topographic map) than the DEM-SRTM and DEM-IBGE obtained by the photogrammetry technique.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…This was observed by Pinheiro et al (2012), who evaluated the quality of the DEM derived from the topographic map, ASTER and SRTM in a qualitative assessment based on the aspects of the surface and a number of spurious depressions, for a DSM in a watershed of 125,078 ha, with relief variation from flat to rugged. These authors observed a better performance of DEM-TM and hybrid DEM (map data + data points extracted from SRTM + points extracted from topographic map) than the DEM-SRTM and DEM-IBGE obtained by the photogrammetry technique.…”
Section: Resultsmentioning
confidence: 90%
“…These were chosen for being the key TA used in DSM (Behrens et al, 2010;ten Caten et al, 2012), having been studied in the DEM evaluation for use in DSM (Pinheiro et al, 2012;Teske et al, 2014) and for being directly related to water movement in the soil, with an influence on the soil formation process (Moore et al, 1993;Wilson and Gallant, 2000).…”
Section: Evaluation Of the Quality Of Elevation Data Of Demsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diferentes interpoladores geoestatísticos, modelos e métodos de classificação permitiram gerar resultados e análises sobre o meio físico, tais como a topografia, erosão, atributos químicos, físicos e tipos de solo (Grego et al, 2012;Miqueloni et al, 2012;Pinheiro et al, 2012;Santi at al., 2012;Sarmento et al, 2012;Valladares et al, 2012;Weber & Fontana et al, 2012). Esses métodos também foram aplicados para análises sobre os recursos hídricos, como evapotranspiração, precipitação, balanço hídrico e bacias hidrográficas (Andrade et al, 2012;Carvalho et al, 2012;Facco et al, 2012;Manzione et al, 2012;Oliveira et al, 2012;Silva et al, 2012). O mapeamento digital das características do solo e da água é fator essencial para o ordenamento territorial e o zoneamento das atividades agropecuárias e representa, ainda, uma fronteira do conhecimento nas ciências agrárias.…”
Section: Pesquisa Desenvolvimento E Inovações Geoespaciais Para a Agunclassified